DEVELOPING MATHEMATICAL COMMUNICATION AND REPRESENTATION OF STUDENTS GRADE VII: A DESIGN RESEARCH - Juandi, Dadang; Jupri, Al (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2013)
This research studies mathematical communication and representation through problem based-learning which is developed by design research. There are two objectives of this research. First, in short term, the research is conducted to know: how studentsâ mathematical communication and representation develops, does classroom culture support the achievement of basic-competence, and what are studentsâ learning obstacles. Second, in long term, this research is conducted to develop âa theoryâ in mathematics education. These two objectives are expected to be achieved through developmental research (in this case using design research). The first objective is achieved by design research which includes three phases: preliminary design, experiment, and retrospective analysis. The preliminary research showed that: (i) mathematical communication and representation could be developed through contextual learning materials, proper teacherâs intervention, various learning-teaching settings, a didactical situation developed by the teacher, and the teacherâs effort in connecting didactical situations i.e., between learning materials and students, and between students and the teacher; (ii) studentsâ difficulties include: a difficulty in communicating mathematical idea verbally, representing mathematical idea algebraically, using mathematical representation to solve problems, and proposing argumentation; and (iii) the teacherâs difficulty is analyzing studentsâ mathematical communication and representations.Key Words: learning obstacles, mathematical communication, mathematical representation, design research